Presence of protein constituents of the gram-positive bacterial phosphotransferase regulatory system in Acholeplasma laidlawii. - Hoischen, C (1993)
Acholeplasma species have been reported to lack a functional phosphoenolpyruvate:sugar phosphotransferase system (PTS). We show here that Acholeplasma laidlawii possesses activities of enzyme I, HPr, HPr(ser) kinase, and HPr(ser-P) phosphatase but lacks detectable activities of enzymes II of the PTS. HPr from this organism was purified, and the regulatory properties of the kinase and phosphatase were characterized and shown to differ from those of previously studied bacteria. The results suggest the presence of an incomplete PTS in A. laidlawii which has the potential to function in a unique regulatory capacity.